A radiological follow-up study of plasma-sprayed fluorapatite (FA) coatings - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2003)
In this paper a radiologic follow-up study of plasma sprayed titanium implants in rams was performed. It is already known that, because of their properties, surface-active ceramics like hydroxyapatite (HA) and bioglass have been used in orthopedic surgery. Because of their low toughness, their use on metal surfaces as coatings has proven more applicable. HA was produced from human teeth. Dentine and enamel flourapatite (DFA and EFA) were separately plasma sprayed on 6.35mm. diameter titanium implants. These produced implants sterilized and implanted in the metaphysis region of the tibia within the unsprayed control group. After circa 2.5 months x-rays were taken and it was noted that no radiolucent areas around the implants evidenced. The soft tissues above the tibias were healed. Thus no inflammation flow was observed. Osseointegration around the implants was verified.
Keywords: hydroxyapatite; fluorapatite; plasma-spraying; implant; animal studies; HYDROXYAPATITE; IMPLANTS